2008
DOI: 10.1093/rpd/ncn047
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance of computed and digital radiography systems

Abstract: Computed radiography (CR) and digital radiography (DR) are replacing traditional film screen radiography as hospitals move towards digital imaging and picture archiving and communication systems (PACS). Both IPEM and KCARE have recently published quality assurance and acceptance testing guidelines for DR. In this paper, the performance of a range of CR and DR systems is compared. Six different manufacturers are included. Particular attention is paid to the performance of the systems under automatic exposure co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
0
11
0
4
Order By: Relevance
“…This study was done to evaluate the effects of different IAC modes on ASW eRD quantification of restoration materials under different exposure conditions. Studies have shown that there are no significant differences in image quality of the various sensor systems currently available 15-18. For the current study, we have used a CMOS based digital radiography system.…”
Section: Discussionmentioning
confidence: 99%
“…This study was done to evaluate the effects of different IAC modes on ASW eRD quantification of restoration materials under different exposure conditions. Studies have shown that there are no significant differences in image quality of the various sensor systems currently available 15-18. For the current study, we have used a CMOS based digital radiography system.…”
Section: Discussionmentioning
confidence: 99%
“…Hierzu wurden subjektive wie auch objektive Bewertungskriterien verwendet. Unter anderem durch die vermehrte Anwendung digitaler Röntgengeräte wurde die Strahlendosis für den Patienten in der Vergangenheit bereits reduziert und die Bildqualität gleichzeitig verbessert [24,25]. Diese Tatsache zeigt auch, dass eine höhere Strahlendosis nicht immer eine bessere Bildqualität bedeuten muss.…”
Section: Messung Des Signal-rausch-verhältnissesunclassified
“…Recommendations from the International Commission on Radiation Protection (ICRP) formed the basis for national and international standards of radiological protection and were accepted by the South African Department of Health Directorate Radiation Control (SADOH DRC) in 2001. 7 Although QA programmes were implemented in 2001 and declared essential, monitoring of the performance of QC tests only became compulsory in SA in 2009. 3 Accredited vendor companies are responsible for ensuring that the QC tests are performed at the prescribed intervals as per regulation of the Directorate Radiation Control (DRC).…”
Section: Introductionmentioning
confidence: 99%